The Liverpool Peritonsillar abscess Score: Development of a predictive score through a prospective multicentre observational study. (14th February 2019) - Lau, Andrew S.; Selwyn, David M.; Yang, Ding; Swainbank, Liam; Ridley, Paul; Carmichael, Nicola; Metcalfe, Christopher; Watson, George; Emerson, Hannah
Abstract : Objectives: While uncommon in the population at large, peritonsillar abscess (PTA) is a common subject of ENT referrals. Missed or uncertain diagnosis is a source of concern for non‐specialist referrers. In line with the NHS England Second Sepsis Action Plan, we aimed to develop a predictive score for the presence of PTA. This would help to improve non‐specialist colleagues' diagnostic certainty as well as to support ENT surgeons' triage of these referrals. Design: Prospective, multicentre observational study. Setting: Primary and secondary care. Participants: Patients >16 years with symptoms of sore throat. Data: We prospectively collected comprehensive data on patient demographics, symptoms and clinical status. We documented whether the patient had aspiration‐proven PTA or not. We performed binary logistic regression analysis, iterative development of a predictive score which we validated internally. Results: 100 patients were included (46 PTA and 54 tonsillitis). Five variables added significantly to the logistic regression model: unilateral sore throat; trismus; male gender; pharyngeal voice change; and uvular deviation. Using the odds ratio outputs, we developed the Liverpool Peritonsillar abscess Score (LPS) iteratively. We validated the latest (third) iteration of the LPS internally (ie, on the same sample), yielding sensitivity 96%; specificity 85%; positive predictive value 85%; and negative predictive value 96%. The area under the receiver operating characteristics (AUROC) curve was 0.970. Conclusions: We have developed the first predictive score for PTA based on symptoms and signs that do not require the user to have specialist experience. Its high negative predictive value may be particularly helpful to non‐specialist colleagues.